2019
DOI: 10.1080/19420862.2019.1690959
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of antibody-mediated complement-dependent cytotoxicity by modulating the intrinsic affinity and binding valency of IgG for target antigen

Abstract: Complement-dependent cytotoxicity (CDC) is a potent effector mechanism, engaging both innate and adaptive immunity. Although strategies to improve the CDC activity of antibody therapeutics have primarily focused on enhancing the interaction between the antibody crystallizable fragment (Fc) and the first subcomponent of the C1 complement complex (C1q), the relative importance of intrinsic affinity and binding valency of an antibody to the target antigen is poorly understood. Here we show that antibody binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Binding of C1q to OFA opsonized cells was thus clearly stronger than for RTX on all tested cell lines, whereas binding of C1q to OBI opsonized cells could not be detected. Bivalent target engagement therefore positively correlates with strong C1q capture for the investigated anti-CD20 IgGs and expanding this analysis to a larger panel of anti-CD20 IgGs would be of interest, as contrasting observations have been made for other antigens ( 19 , 37 ). The real-time binding assay presented in this study also allowed to resolve the presence of two interactions, as well as their kinetic and affinity values for C1q binding to anti-CD20 IgG opsonized cells.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Binding of C1q to OFA opsonized cells was thus clearly stronger than for RTX on all tested cell lines, whereas binding of C1q to OBI opsonized cells could not be detected. Bivalent target engagement therefore positively correlates with strong C1q capture for the investigated anti-CD20 IgGs and expanding this analysis to a larger panel of anti-CD20 IgGs would be of interest, as contrasting observations have been made for other antigens ( 19 , 37 ). The real-time binding assay presented in this study also allowed to resolve the presence of two interactions, as well as their kinetic and affinity values for C1q binding to anti-CD20 IgG opsonized cells.…”
Section: Discussionmentioning
confidence: 98%
“…For anti-EGFR mAbs it has been shown that monovalent target engagement results in higher CDC efficacy. This could be a consequence of monovalent binding resulting in a higher number of IgGs bound and this, in turn, might increase the likelihood for the formation of multimeric IgG-Fc platforms suitable for C1q binding ( 37 ). For anti-CD20 mAbs, on the other hand, bivalent binding might enhance crosslinking of CD20 and thus lead to more efficient clustering of CD20 and bound mAbs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 25 However, the notion that bivalent binding correlates with CDC efficacy is contradicted by previous studies that found changing one of the Fab arms of anti-epidermal growth factor receptor antibodies to an irrelevant binding epitope, and thereby making them functionally monovalent, enhanced the CDC capacity of these antibodies compared to their parental version. 10 , 30 It is possible that the optimal binding mode for efficient complement activation differs for mAbs targeting different receptors.…”
Section: Discussionmentioning
confidence: 99%